Features of Microsystems for Cultivation and Characterization of Stem Cells with the Aim of Regenerative Therapy. (31st January 2016) - Ahn, Kihoon; Kim, Sung-Hwan; Lee, Gi-Hun; Lee, SeungJin; Heo, Yun Seok; Park, Joong Yull
Abstract : Stem cells have infinite potential for regenerative therapy thanks to their advantageous ability which is differentiable to requisite cell types for recovery and self-renewal. The microsystem has been proved to be more helpful to stem cell studies compared to the traditional methods, relying on its advantageous feature of mimicking in vivo cellular environments as well as other profitable features such as minimum sample consumption for analysis and multiprocedures. A wide variety of microsystems were developed for stem cell studies; however, regenerative therapy-targeted applications of microtechnology should be more emphasized and gain more attractions since the regenerative therapy is one of ultimate goals of biologists and bioengineers. In this review, we introduce stem cell researches harnessing well-known microtechniques (microwell, micropattern, and microfluidic channel) in view point of physical principles and how these systems and principles have been implemented appropriately for characterizing stem cells and finding possible regenerative therapies. Biologists may gain information on the principles of microsystems to apply them to find solutions for their current challenges, and engineers may understand limitations of the conventional microsystems and find new chances for further developing practical microsystems. Through the well combination of engineers and biologists, the regenerative therapy-targeted stem cell researches harnessing microtechnology will find better suitable treatments for human disorders.